Ecological modernisation and nature conservation. (24th February 2004) - van Koppen, C.S.A. (Kris)
Although ecological modernisation has a prominent position in contemporary environmental sociology, efforts to use ecological modernisation concepts in the specific case of nature conservation are remarkably absent. This article explores the potentials of applying ecological modernisation as a discourse and as a theory to issues of nature management. It is argued that ecological modernisation theory offers interesting perspectives for analysing actual developments in nature and biodiversity conservation. From an ecological modernisation perspective, nature conservation emerges both as resource conservation and as cultural consumption. Social research into multifunctional land use and into new economic actors and market dynamics in conservation fits in well with the hypotheses of ecological modernisation theory, and this theory can be very helpful in analysing the links between production and consumption practices and issues of nature conservation. The central concept of ecological rationality, however, would need to be broadened in order to encompass the socio-cultural drivers of consumers and citizens dealing with nature.